Disaggregation of Productivity Growth of Indonesian Airports - Viverita, Viverita; Kusumastuti, Ratih Dyah (The South East Asian Journal of Management, 2015)
This paper reports the sources of productivity growth of 23 Indonesian airports foryears 2006-2010. Using input slack-based productivity index (ISP), we disaggregatetotal factor productivity change into each input productivity change. Apron areaand terminal area are chosen as input variables while aircrafts’ movement is theoutput. By classifying the airports based on two operators, this study finds thatairports under the management of Angkasa Pura 1 (AP1) show higher productivitygrowth than Angkasa Pura 2 (AP2), whose growth is mainly driven by technicalprogress in apron areas. Moreover, the productivity decline of AP2 was mostlydue to inefficient use of terminal areas.